Effect of oxytetracycline on biogas production and microbial communities during anaerobic digestion of cow manure by fluorescence in situ hybridization and real time polymerase chain reaction - Ertekin, Emine. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2011., 2011)
Antibiotics used in veterinary practice end up in animal manure and present a threat to biogas production from substrates as such, for they are possibly detrimental to the fragile microflora of anaerobic digestion processes. In this study, inhibitory effects of a commonly used veterinary antibiotic, oxytetracycline on anaerobic digestion of cow manure is examined. Within the context, digester performances in terms of biogas and methane productions, and microbial dynamics were monitored. In this study, two batchwise experiment sets were conducted in serum bottles. In both sets OLR was maintained at 1.4 kgTVS/m3d and HRTs were 60 and 30 days in Set 1 and Set 2 respectively. TS concentration was kept at 5%. In both sets, total methane yields were between 87-90 L/kgTVS with a methane percentage of (58±5)%. In Set 1, OTC in concentrations of 50 mg/L, 100mg/L and 200 mg/L were added to serum bottles operating with non medicated manure. Biogas production continued untill 30 days in the control serum bottle up to a volume of 315 mL and inhibitions were 41%, 57% ve 61% in serum bottles containing 50, 100 and 200 mg/L OTC respectively. IC50 value of the drug was calculated as 68 mg/L. It was recorded that inhibitory effect of OTC regressed during the operation and serum bottle operated with 50 mg/L OTC could reach the values of control bottle at after 60 days. Thereby, in this serum bottle OTC toxicity fitted in with non-competitive inhibition model. In all of the bottles, the majority of the active Archaea was hydrogenotrophic and Methanobacteriales was the dominant order. Acetoclastic methanogens were represented by the members of Methanosarcinaceae family. It was encountered that acetoclastic methanogens decreased significantly by the increased concentrations of OTC, therefore inhibitions in biogas and methane productions were correlated with the decrease of this group. It was found out that changes in the total 16S rDNA copy numbers of bacteria, Archaea and methanogens were not effective in explaining the case of OTC toxicity. In Set 2, a dairy cow was medicated with 20 mg/kg body weight OTC and manure samples collected on days 1, 2, 3, 5, 10, 15 and 20 after medication, were used as substrate in serum bottles. It was found out that, 10% of the OTC injected to the animal was excreted in manure. Biogas production continued in the control serum bottle until day 30 of the operation to a final volume of 255 mL. The most severe inhibitions at this stage were monitored in serum bottles operated with manure collected on the 2nd and 3rd days after medication which were 60% and 57%. In this set majority of the active Archaea was also hydrogenotrophic and Methanomicrobiales was the abundant hydrogentrophic methanogen in the serum bottles. Acetoclastic methanogens were represented by the members of Methanosarcinaceae family. It could be observed that Methanomicrobiales was the most effected group from OTC in medicated manure in the early stages of the digestion, however as the operation progressed Methanosarcinacea was also effected. It was found that changes in the total 16S rDNA copy numbers of the domains Archaea, bacteria and methanogens were not significantly effected by the inhibitory effect of OTC in medicated manure.
Keywords: Biogas.; Oxytetracycline.; Sewage -- Purification -- Anaerobic treatment.